Educational Opportunities and Geographical Distribution of Degree Teachers in Saskatchewan - Walmsley, P.; Ohtsu, M. (Relations industrielles / Industrial Relations, 1980)
The purpose of this study is to examine the historical trend on the distribution of teacher skillmix between 1957 and 1974 in the light of certain changes in the socio-economic setting surrounding employment of teachers which occured during the period.